ANALISIS KEPERCAYAAN NASABAH PENGGUNA ATM - Yeni Dwi Meilianasari (Manajemen Bisnis, 2012)
ANALISIS KEPERCAYAAN NASABAH PENGGUNA ATMYeni Dwi MeilianasariJurusan Manajemen Fakultas Ekonomi UMME-mail: yeni.meili@gmail.comABSTRACTThis study aims to determine the user’s ATM customer Trust and ability to determine the effect ofvariables, variable benevolence, and variable integrity of customer Trust. The respondents are consumerof the Bank. Data collecting uses questionnaires and distributed to ATM customer who haveused it for their daily transaction. The analysis tool used is a logistic regression analysis. Surveyresults reveal that the variable ability, benevolence variables significantly influence the integrity ofcustomer Trust. The most dominant variable is the variable effect of kindness. This research customermust know the things offered by the bank and the bank until there arose a belief in the bank willchoose to save their money.Keywords: ability, benevolence, integrity, and customer trust.